‘Toutes les femmes qui souffrent’ - A specific critical perspective on the female figures of the 38th edition of the Printemps des Comédiens Festival in Montpellier (May 30 - June 21, 2024) - Milella , Massimo (Sinais de Cena, 2024)
Crítica ao Festival Printemps des Comédiens 2024